2012
DOI: 10.1051/0004-6361/201219005
|View full text |Cite
|
Sign up to set email alerts
|

A population of isolated hard X-ray sources near the supernova remnant Kes 69

Abstract: Recent X-ray observations of the supernova remnant (SNR) IC 443 interacting with molecular clouds detected a new population of hard X-ray sources related to the remnant itself, which has been proposed to be fast ejecta fragments propagating within the dense environment. Encouraged by these studies, we obtained a deep XMM-Newton observation of the SNR Kes 69, which also shows signs of a shock-cloud interaction. We report on the detection of 18 hard X-ray sources in the field of Kes 69, which is a number sognifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In the soft X-ray band (0.5-2.0 keV), we see clear emission associated with the SNRs, while in the hard X-ray band of 5.0-8.0 keV, no structure accompanied with the soft band is found. Thus, all these SNRs are soft Xray sources with electron temperature of 0.8 keV, which are confirmed in Sawada & Koyama (2012), Bocchino et al (2012), Bamba et al (2016), and Uchida et al (2012) for W28, Kes 69, Kes 78, and W44, respectively. Kes 67 is also a soft X-ray source with an electron temperature of ∼ 0.4 keV .…”
Section: X-ray Spectra From the Fe I Kα-enhanced And Reference Regionssupporting
confidence: 66%
See 1 more Smart Citation
“…In the soft X-ray band (0.5-2.0 keV), we see clear emission associated with the SNRs, while in the hard X-ray band of 5.0-8.0 keV, no structure accompanied with the soft band is found. Thus, all these SNRs are soft Xray sources with electron temperature of 0.8 keV, which are confirmed in Sawada & Koyama (2012), Bocchino et al (2012), Bamba et al (2016), and Uchida et al (2012) for W28, Kes 69, Kes 78, and W44, respectively. Kes 67 is also a soft X-ray source with an electron temperature of ∼ 0.4 keV .…”
Section: X-ray Spectra From the Fe I Kα-enhanced And Reference Regionssupporting
confidence: 66%
“…The point source in the south-west of W28 is reported by Pannuti et al (2017); the object, CXOU J175857.55-233400.3, is likely a cataclysmic variable or a quiescent lowmass X-ray binary. Two point-like sources located in the north and the west of Kes 69 are reported by Bocchino et al (2012). However no further information on these sources is available.…”
Section: X-ray Spectra From the Fe I Kα-enhanced And Reference Regionsmentioning
confidence: 99%
“…The observed hard spectra and enhanced abundances suggest that these may be fast-moving knots of ejecta traveling into dense molecular material and producing Kα emission accompanied by nonthermal bremsstrahlung (NTB) emission from shock-accelerated electrons (Bykov 2002). Knots with similar spectral properties are observed in Kes 69 and are coincident with CO emission from a nearby MC (Bocchino et al 2012), reinforcing this interpretation. Discrete X-ray knots directly along the SNR/MC interaction region in 3C 391 are also observed (Chen et al 2004), but while the inferred density for these knots is high, consistent with structures being driven into clouds, the abundances do not show strong evidence for metal enhancements.…”
Section: Abundances and Nonthermal Emissionmentioning
confidence: 58%
“…This has motivated a dedicated XMMNewton observation of Kes 69 (Obs ID: 0605480101 PI: Miceli). For searching the evidence of fast ejecta propagating in a dense environment, a recent study has revealed 18 hard X-ray point sources in the field of Kes 69 with this XMMNewton observation (Bocchino et al 2012). Investigations of their source nature suggest these hard X-ray sources can possibly be fast ejecta fragments or cataclysmic variables (CVs).…”
Section: Introductionmentioning
confidence: 81%